Herbicides in surface water bodies - behaviour, effects on aquatic organisms and risk assessment - Stevanovic, Marija; Gašić, Slavica (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2020)
Pesticides play a very important role in reducing losses and maintaining quality in crop production. Although positive effects of pesticide use are undeniable, adverse effects are frequent. This has led to a comprehensive reevaluation of the benefits of pesticide use and potential adverse effects on human health and the environment before placing them on the market. The fact that pesticides are designed to be toxic and are deliberately introduced into the environment, makes them a very important and strictly regulated group of pollutants. The most commonly used group of pesticides are herbicides, and their detection in surface water bodies has been repeatedly reported. In spite of being designed to be toxic to target species, adverse effects on other inhabitants of aquatic environments have also been observed. In order to prevent negative environmental effects, the registration process for active substances and plant protection products involves predictive environmental risk assessments (ERA). Reliable assessment of long-term effects on non-target species, natural populations and ecosystems is a priority and ERA process is constantly being improved.